Perfect for the beach - Foster, Lori; Denison, Janelle; McCarthy, Erin; Davidson, Mary Janice; Perrin, Kayla; Leigh, Morgan (New York : Kensington Books, 2004)
Temperatures will rise in this sultry collection of six novellas that includes Lori Foster's Some Like It Hot, in which Dr. Cary Rupert is unable to deny his attraction to sexy patient Nora Chilton, along with other works by Kayla Perrin, Janelle Denison, Erin McCarthy, MaryJanice Davidson, and Morgan Leigh.
Murphy's law / Morgan Leigh
Keywords: Beaches -- Fiction; Man-woman relationships -- Fiction; Love stories